2010
DOI: 10.5194/angeo-28-1463-2010
|View full text |Cite
|
Sign up to set email alerts
|

Size of the coming solar cycle 24 based on Ohl's Precursor Method, final estimate

Abstract: Abstract. In Ohl's Precursor Method (Ohl, 1966(Ohl, , 1976, the geomagnetic activity during the declining phase of a sunspot cycle is shown to be well correlated with the size (maximum sunspot number Rz(max)) of the next cycle. For solar cycle 24, Kane (2007a) used aa(min)=15.5 (12-month running mean), which occurred during March-May of 2006 and made a preliminary estimate Rz(max)=124±26 (12-month running mean). However, in the next few months, the aa index first increased and then decreased to a new low value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…So far they are more likely to be the right ones, because the later experimental observations during the cycle 23/24 minima and after the initiation of SC24 have indicated a potentially weak cycle. Some estimations of the new cycle have therefore been updated to an ultra low level (e.g., Kane, 2010). The observed SSN of the 36th month (November 2011) of SC24 is 61.1 and obviously lower than the 90.5 of SC23 (May 1999), from which Kane (2013) predicted that SC24 will have a maximum amplitude of about 77.0 ± 13.4.…”
Section: Introductionmentioning
confidence: 99%
“…So far they are more likely to be the right ones, because the later experimental observations during the cycle 23/24 minima and after the initiation of SC24 have indicated a potentially weak cycle. Some estimations of the new cycle have therefore been updated to an ultra low level (e.g., Kane, 2010). The observed SSN of the 36th month (November 2011) of SC24 is 61.1 and obviously lower than the 90.5 of SC23 (May 1999), from which Kane (2013) predicted that SC24 will have a maximum amplitude of about 77.0 ± 13.4.…”
Section: Introductionmentioning
confidence: 99%
“…The amplitudes of solar cycle 24 predicted by researcher are quite dispersed (Obridko and Shelting 2008;Pesnell 2008;Bhatt et al 2009;Ajabshirizadeh 2011;Chumak and Matveychuk 2010;Dabas and Sharma 2010;Du and Wang 2010;Kane 2010;Wang et al, 2002Wang et al, , 2008Wang et al, , 2009). However, a dynamo model tends to predict that the amplitude of solar cycle 24 is about 90 or even at less than 90 (Jiang et al 2007).…”
Section: Summary and Discussionmentioning
confidence: 97%
“…A high correlation can be used to estimate the strength of a new solar cycle [9][10][11][12][13][14][15][16][17]. For example, Ohl's geomagnetic precursor method [18] succeeded in predicting R max in cycles 20-22 [19][20][21][22] due to the high correlation coefficients (> 0.8) between R max and geomagnetic-based parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Kane [9] 58 ±25 aa minimum Choudhuri et al [ [32] 165 ±15 flux-transport dynamo model a low level before rising (as shown in the most spotless days since cycle 16 [28,29]), cycle 24 is unusual, which is drawing greater attention than ever. Besides, as solar dynamo models have begun to be applied in predicting R max [30][31][32], the predictions of the strength of cycle 24 attract special attention in order to test the predictive skill of solar dynamo models.…”
Section: Authormentioning
confidence: 96%